Big data Analytics Capability Effect on Indonesia Firm Performance: The Mediating Role of Business Process Agility - Kusbianto, Nugraha; Darmawan, Ari (Accounting Department,, 2024)
Purpose: This study aims to investigate the impact of Big Data Analytics Capabilities (BDAC) on Indonesian Firm Performance (FPER), addressing the lack of empirical research in this area despite Indonesia's significant Big Data expenditure growth. The study also proposes a conceptual model as a framework for developing BDAC. Method: This is a quantitative study conducted in Indonesia using purposive and snowball sampling techniques to collect data from 51 Indonesian companies. The research model is based on the IT Capability framework, Sociomaterialism Theory, and incorporates Business Process Agility (BPA) as a mediating variable, as suggested by previous research. Findings: The results demonstrate a significant positive impact of BDAC on FPER. Furthermore, the study confirms that BPA significantly mediates the relationship between BDAC and FPER, highlighting the crucial role of agile business processes in leveraging the benefits of Big Data Analytics for improved firm performance. Practical Implications: This research provides valuable insights for Indonesian companies by: 1) demonstrating the significant positive impact of investing in BDAC on firm performance; 2) highlighting the importance of developing agile business processes to maximize the return on Big Data Analytics investments; and 3) offering a conceptual framework for developing and enhancing BDAC within Indonesian organizations. Originality: This study contributes to the existing literature by: 1) providing empirical evidence on the impact of BDAC on FPER specifically within the Indonesian context; 2) proposing a novel conceptual model for developing BDAC based on a combination of IT Capability framework, Sociomaterialism Theory, and the mediating role of BPA; and 3) addressing the gap in research on the relationship between BDAC and FPER in the Indonesian market. Paper Type: This research can be classified as an empirical study within the field of Information Systems, specifically focusing on Big Data Analytics, firm performance, and business process management. Keywords: Big Data, Firm Performance, Business Process Agility